Exploring Language Variations in Communication between Sellers and Buyers - Suktiningsih, Wiya; Widani, Ni Nyoman; Putri Nila Sudewi, Ni Ketut; Supatmiwati, Diah (Lexeme : Journal of Linguistics and Applied Linguistics, 2024)
As part of a community, we use language to interact and communicate with other group members, in various speech events. The use of language to speak is a form of cultural practice to share ways of doing things, ways of speaking, beliefs and values. Cultural and linguistic diversity can show where we come from and what kind of community we live in. One of the domains where speakers from various backgrounds carry out social interactions is traditional markets. Buyers and sellers from various backgrounds communicate to carry out transactions until reaching an agreement on price. The variety of languages ​​used by sellers and buyers when interacting to agree on prices is of interest to researchers. The research method used is descriptive qualitative using a sociolinguistic approach, to see the relationship between language use and the community at the location of the speech event. The research location was carried out at the Pagutan market, which is located in a Sasak-majority area, but is now the area of ​​choice for immigrants from various regions. The results of this research show that the variety of languages ​​used at Pagutan Mataram Market is influenced by the way we speak and also pays attention to socio-cultural background, age, gender, race and social status.